Systematic Construction of Articles of Criminal Defamation In the ITE Law - Ega Rizky Pangastuti (Jurnal Hukum Khaira Ummah, 2022)
Court decisions can be seen as the laboratory of logic after considering (legal reasoning) the legal facts that appear in court. The criminal defamation article has become a controversial law because of its elastic interpretation. The purpose of this article is to examine and analyze the systematic construction of the defamation article and its juridical consequences in article 27 paragraph (3) of Law No.19 of 2016 concerning Electronic Information and Transactions. The method used is normative juridical and analytical orientation using a conceptual approach (Concept Approach) and a statutory approach (Statue Approach). The conclusion of the research is that the systematic construction of criminal defamation articles is formulated first: legal subjects (adresat), second: acts or criminal acts, third: criminal sanctions (jail and fines). The phrase “transmitted” is an extensive juridical formulation/formulation in accordance with the phrase “in public” as formulated in the Criminal Code. Disgraceful acts are formulated cumulatively (the word “and”) include intentionally and without rights (1) distributing and/or (2) transmitting and/or (3) making accessible Electronic Information and/or Electronic Documents. The formulation of the action convicted is cumulative-alternative marked by the phrase "and/or". The juridical weakness of this law is that there is no determination of the offense as a "crime" or "violation". This fact can be interpreted as the skepticism of legislators in the criminal approach in the ITE Law. The juridical consequence of the application of this article is the provision of a complaint offense. It is recommended that the formulation of the complaint offense follow the principle of harmonization of the main criminal law system (KUHP).Keywords: Systematic Construction of Criminal Articles, Defamation